Assessment of Anxiety and Depression among Caregivers of Mentally Ill Patients Attending Mental Hospital, Lalitpur, Nepal - Mishra, Durga Khadka; Shakya, Urusha (Journal of Nepal Health Research Council, 2021)
Background: Family take the role of caregivers and provide the mentally ill member with help, care and support. Caregivers are at the high risk to anxiety and depression. The main objective of the research was to assess anxiety and depressive status among caregivers of mentally ill patients attending Mental Hospital, Lalitpur, Nepal. Methods: A cross sectional study based on clinical setting was conducted among 184 caregivers of mentally ill patients attending outpatient department of Mental Hospital, Lagankhel, Lalitpur, Nepal. Purposive sampling technique was used for the study. Pre-tested semi-structured questionnaire and validated Nepali translated version of hospital anxiety and depression scale was used to assess anxiety and depressive status among caregivers. The collected data was entered in Microsoft Excel 2013 and data analysis was done in Statistical Package for Social Sciences (SPSS) international business machine version 25. Ethical consideration was maintained during the study. Results: Anxiety and depressive symptoms among caregivers of mentally ill patients was 24.5% and 19.6% respectively. Risk factors significantly associated with anxiety and depressive symptoms in caregivers were sex of caregiver, socio-economic status and sex of patient. Types of mental illness of patient was also significantly associated with anxiety while educational status was significantly associated with depressive symptoms in caregivers. Conclusions: Anxiety and depressive symptoms were found among caregivers of mentally ill patients. It is high time to consider mental health of caregiver and mental health promotion programs and policies for caregivers should be implemented. Keywords: Anxiety; caregiver; depression; mentally ill patient; Nepal